Relation between muscarinic receptor cationic current and internal calcium in guinea-pig jejunal smooth muscle cells. - Pacaud, P (1991)
1. The action of carbachol, which activates muscarinic receptors, was studied in single patch-clamped cells where free internal calcium concentration in the cell (Cai2+) was estimated using the emission from the dye Indo-1. Cells were dialysed with potassium-free caesium solution to block any Ca(2+)-activated K(+)-current. 2. Carbachol applied to the cell evoked an initial peak in Cai2+ followed by a smaller sustained rise (plateau) upon which several oscillations in Cai2+ were often superimposed; the changes in inward, cationic current (icarb) followed changes in Cai2+ closely. Calcium entry blocker did not affect these responses. 3. The initial peak in Cai2+ produced by carbachol was due to calcium store release: it was essentially unchanged at +50 mV, and abolished by prior application of caffeine (10 mM) to the cell or by inclusion of heparin (which blocks D-myoinositol 1,4,5-trisphosphate receptors) in the pipette. In contrast, the rise in Cai2+ produced by ATP in rabbit ear artery smooth muscle cells was unaffected by caffeine or heparin as it was due to calcium entry into the cell. 4. The later sustained rise (plateau) in Cai2+ produced by carbachol was due to the entry of calcium into the cell down its electrochemical gradient as it was affected by changing the cell membrane potential or the calcium concentration of the bathing solution. As the sustained rise in Cai2+ produced by caffeine had similar properties, it was suggested that depletion of calcium stores can evoke an increased calcium entry into the cell through some pathway. 5. The cationic current evoked by carbachol was strongly dependent on Cai2+. It was small if any rise in Cai2+ due to calcium store release was prevented by the inclusion of heparin in the pipette solution and increased greatly if calcium entry was provoked through voltage-dependent channels by applying a depolarizing pulse or if calcium was released from stores by caffeine. 6. In the longitudinal muscle of guinea-pig small intestine, activation of muscarinic receptors by carbachol results in the opening of cationic channels; the resulting depolarization increases the frequency of action potential discharge and this determines the degree of contraction. Muscarinic receptor activation opens cationic channels by two mechanisms: release of stored calcium increases Cai2+ and this strongly potentiates a primary mechanism which may involve a G-protein.